Chernobyl cleanup workers from Estonia: cohort description and related epidemiological research. (29th October 2015) - Rahu, Kaja; Rahu, Mati; Tekkel, Mare; Veidebaum, Toomas; Hakulinen, Timo; Auvinen, Anssi; Bigbee, William L; Hartshorne, Michael F; Inskip, Peter D; Boice, John D
Abstract: The Estonian study of Chernobyl cleanup workers was one of the first investigations to evaluate the possible health consequences of working in the Chernobyl area (the 30 km exclusion zone and/or adjacent territories) after the 1986 reactor accident. The cohort consists of 4831 men who were dispatched in 1986–1991 for tasks involving decontamination, construction of buildings, transport, radiation measurement, guard duty or other activities. By 31 December 2012, the follow-up of the cohort yielded 102 158 person-years of observation. Exposure and health data were collected by postal questionnaires, biodosimetry evaluations, thyroid screenings, and record-linkages with cancer, causes of death and health insurance reimbursement registers and databases. These data cover socio-demographic factors, employment history, aspects of health behaviour, medical history, work and living conditions in the Chernobyl area, biomarkers of exposure, cancer and non-cancer disease occurrence and causes of death. Cancer incidence data were obtained for 1986–2008, mortality data for 1986–2011 and non-cancer morbidity data for 2004–2012. Although the cohort is relatively small, it has been extensively examined and benefited from comprehensive nationwide population and health registers. The major finding was an increased risk of suicide. Thyroid examinations did not reveal an association with thyroid nodular disease and radiation dose, but did indicate the importance of accounting for screening when making comparisons with unscreened populations. No risk of leukaemia was observed and risks higher than 2.5-fold could be excluded with 95% confidence. Biodosimetry included GPA analyses and chromosomal translocation analyses and indicated that the Estonian cleanup workers experienced a relatively low mean exposure of the order of 0.1 Gy. One value of the Estonian study is in the methodologic processes brought to bear in addressing possible health effects from the Chernobyl accident. Twenty-five years of research are summarised and opportunities for the future listed.